2019
DOI: 10.7759/cureus.5661
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Screening During Early Pregnancy and the Need for Trimester Specific Reference Ranges: A Cross-Sectional Study in Lahore, Pakistan

Abstract: BackgroundDerangements in thyroid hormone levels can cause multiple complications in the mother and the foetus. Thyroid stimulating hormone (TSH) and free thyroxine (free T4 or FT4) levels are used to screen for maternal thyroid dysfunction; these should be compared with population based trimester-specific reference ranges. Our goal was: to determine the prevalence of various thyroid derangements, in early pregnancy, according to the current reference ranges available; to determine the need for trimester speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…Attempting to account for thyroid disorder in relation to socioeconomic class, Talat, et al did not show any association between income level and thyroid hormone levels [ 26 ]. However, they did note that most of the subjects in their study had free access to healthcare and regular checkups, which may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempting to account for thyroid disorder in relation to socioeconomic class, Talat, et al did not show any association between income level and thyroid hormone levels [ 26 ]. However, they did note that most of the subjects in their study had free access to healthcare and regular checkups, which may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a Pakistani population’s prevalence of overt hypothyroidism was approximately 4%, while a study on northern Indian women showed a prevalence of 7%. The authors attributed differences in diet to partially account for this apparent disparity [ 26 , 27 ]. Furthermore, studies in China have shown variation in thyroid hormone levels in different races [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of thyroid status during pregnancy is of utmost importance for the initiation of treatment of newly diagnosed patients as well as for dose adjustment of patients already on hormone therapy. A decrease in the upper and lower limit of TSH has been noticed in pregnant females compared to the healthy nonpregnant population [13]. In clinical practice, measurement of free T4 and TSH, exceptionally the cut-off values for lower Free T4 and upper TSH reference limit provides the data for evaluating thyroid functioning in population.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of maternal hypothyroidism in iodine-rich areas is Hashimoto's thyroiditis, whereas, in iodine-de cient areas like Pakistan, it is iodine de ciency [11]. A study conducted by Elahi et al in Lahore, Pakistan, revealed that around 79% of the pregnant females were iodine de cient, and 31% had goiter [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these functions are summarized in Table 1. (Khan et al, 2020) They assist in the growth, development and differentiation of all the body cells (Hofstee et al, 2019;Talat et al, 2019). They are a key regulator of the Basal Metabolic Rate (BMR) which is one of the major components of energy expenditure.…”
Section: Introductionmentioning
confidence: 99%